A Critically Endangered new dragonfly species from Morocco: Onychogomphus boudoti sp. nov. (Odonata: Gomphidae) - Ferreira, Sónia; Velo-Antón, Guillermo; Brochard, Christophe; Vieira, Cristiana; Alves, Paulo Célio; Thompson, David J.; Watts, Phillip C.; Brito, José Carlos (Zootaxa, 2014)
Both sexes of Onychogomphus boudoti sp. nov. Ferreira (Odonata: Anisoptera: Gomphidae) and exuviae are described and illustrated from a single locality in Morocco. This newly discovered species differs markedly from other Onychogomphus species by the morphology of the male epiproct and the female vulvar scale. It is genetically distinct in the mitochondrial DNA and the nuclear PRMT gene from all other Western Palaearctic Onychogomphus species. The known distribution of the new species is confined to a small stream with unusual habitat characteristics in the vicinity of Khenifra, in the Middle Atlas, where it experiences low population size and limited genetic diversity. We suggest listing this species both locally and globally as “Critically Endangered” [CR (B1, B2 + abiii)] following the IUCN Red List Categories and Criteria.